Linking collective action to non-timber forest product market for improved local livelihoods: challenges and opportunities - Komarudin, Heru; Siagian, Y.; Oka, N.P. (International Food Policy Research Institute, 2007)
The paper draws on findings from research in South Sulawesi and Jambi Provinces, Indonesia, looking at the role of collective action in helping two local community groups enhance their bargaining power vis a vis other market players (such as collectors, small- and large-scale industries) and promote an increased demand for non-timber forest products. The first group has traditionally collected rattan (Calamus sp) from surrounding forests and was struggling to sell their products at a better price amid market uncertainties and the lack of supportive government policies. The second one was involved in the propagation of another high-value rattan species, widely known as Dragon Blood (Daemonorops sp), in anticipation of an increased market demand for this product. The paper describes challenges and opportunities for the country's forestry decentralization and marketing of forest products, and the role of collective action in improving groups' access to government resources and markets. It also discusses the research team's part in facilitating the groups and highlights the strengths of participatory action research approach in fostering collective action among local stakeholders.